دور قواعد السلوك المهني للمحاسبين في تعزيز جودة المعلومات المحاسبية: role of the rules of professional conduct for accountants in enhancing the quality of accounting information - مجدي البناني; فيلالي حمزة; فنور هدى (Journal of North African Economies, 2025)
This study aims to know the role of the rules of professional conduct for accountants in enhancing the quality of accounting information and making it reflect the real status of performance and the financial position of economic institutions in Algeria, and to address this problem it was necessary to study the correlation and impact of the variable of the rules of professional behavior for accountants and what it contains of dimensions with the variable of quality of accounting information, and to enhance this perception, a questionnaire was designed and distributed to the study sample, the size of which was 259 individuals. Depending on the analytical descriptive approach, the study concluded several results, most notably that there is a role for the rules of professional conduct for accountants in enhancing the quality of accounting information for economic institutions. rules of professional conduct.